Very Small Embryonic-Like Stem Cells, Endothelial Progenitor Cells, and Different Monocyte Subsets Are Effectively Mobilized in Acute Lymphoblastic Leukemia Patients after G-CSF Treatment - Andrzej Eljaszewicz; Lukasz Bolkun; Kamil Grubczak; Malgorzata Rusak; Tomasz Wasiluk; Milena Dabrowska; Piotr Radziwon; Wojciech Marlicz; Karol Kamiński; Janusz Kloczko; Marcin Moniuszko (Stem Cells International)
Background. Acute lymphoblastic leukemia (ALL) is a malignant disease of lymphoid progenitor cells. ALL chemotherapy is associated with numerous side effects including neutropenia that is routinely prevented by the administration of growth factors such as granulocyte colony-stimulating factor (G-CSF). To date, the effects of G-CSF treatment on the level of mobilization of different stem and progenitor cells in ALL patients subjected to clinically effective chemotherapy have not been fully elucidated. Therefore, in this study we aimed to assess the effect of administration of G-CSF to ALL patients on mobilization of other than hematopoietic stem cell (HSCs) subsets, namely, very small embryonic-like stem cells (VSELs), endothelial progenitor cells (EPCs), and different monocyte subsets. Methods. We used multicolor flow cytometry to quantitate numbers of CD34+ cells, hematopoietic stem cells (HSCs), VSELs, EPCs, and different monocyte subsets in the peripheral blood of ALL patients and normal age-matched blood donors. Results. We showed that ALL patients following chemotherapy, when compared to healthy donors, presented with significantly lower numbers of CD34+ cells, HSCs, VSELs, and CD14+ monocytes, but not EPCs. Moreover, we found that G-CSF administration induced effective mobilization of all the abovementioned progenitor and stem cell subsets with high regenerative and proangiogenic potential. Conclusion. These findings contribute to better understanding the beneficial clinical effect of G-CSF administration in ALL patients following successful chemotherapy.